Featured Cover. (10th November 2020) - Li, Lianfu; Zhang, Xin; Luan, Zhendong; Du, Zengfeng; Xi, Shichuan; Wang, Bing; Cao, Lei; Lian, Chao; Yan, Jun
Abstract : The cover image is based on the Research Article In situ Raman quantitative detection of methane concentrations in deep‐sea high‐temperature hydrothermal vent fluids by Lianfu Li et al., https://doi.org/10.1002/jrs.5981 .